Psychometric properties of the Behavioural Outcomes of Anxiety questionnaire in stroke patients with aphasia. (March 2017) - Eccles, Alicia; Morris, Reg; Kneebone, Ian
Objective: To evaluate the psychometric properties of an observational, carer-completed anxiety screen for aphasic stroke patients. Design: Phase 1: A cross-sectional questionnaire design to establish psychometric properties. Phase 2: A randomized longitudinal design with treatment and control to evaluate sensitivity to change and repeatability/reliability. Subjects: Phase 1: 111 patient-carer dyads were recruited through stroke charities: patient mean age 69.7(10. 7), 6.2(5. 2) years since stroke, 76 male; carer mean age 64.7(12. 2), 27 male. Phase 2. A subsample of 50 dyads (29 completed). Measures: All patients completed the Tension Rating Circles and the Frenchay Aphasia Screening Test. Carers completed the Behavioural Outcomes of Anxiety questionnaire, observational versions of the Hospital Anxiety and Depression Scale (HADS-A) and the Generalised Anxiety Disorder-7, and a feedback questionnaire. Intervention: Phase 2: 25 dyads were offered relaxation training and 25 acted as controls. Results: The Behavioural Outcomes of Anxiety questionnaire correlated .77 with the HADS-A and Cronbach's Alpha was .82 demonstrating validity and internal consistency. Using HADS-A cut-off > 7 as criterion the area under the curve was 0.90 and at cut-off of > 16 sensitivity (0.85) and specificity (0.85) were both good. Scores declined significantly more in a group given anxiety training ( n = 12) than in a control group ( n = 17), demonstrating sensitivity to change and construct validity. Two-week repeatability/reliability was .92. Feedback suggested the scale was acceptable. Conclusions: The Behavioural Outcomes of Anxiety questionnaire shows promise as an anxiety screen for stroke patients with aphasia and is sensitive to change. Further analysis of dimensionality and discriminant validity is needed.